A cross-sectional study of achievement motivation among Hong Kong adolescents. - Ngan, Cherrica Ming Mei. (2010)
In contemporary achievement goal research literature, there have been few studies concerning the antecedents of various goal endorsements in the Asian social context. The present research aims at investigating two antecedents of goal endorsement: culture and developmental (age/grade) differences. Specifically, the study researched into the achievement goal endorsement of two different age groups (primary school and secondary school students) in Hong Kong Chinese students. Culture wise, the present research tested the fit of the hierarchical model. In addition, it contributed to the research area by modifying the hierarchical model with an Asian constructed socially oriented achievement goal(SOAG). It was found that the hierarchical model (Elliot & Mcgregor, 1997) applied satisfactorily in this collectivist context. The modified hierarchical model was also found good fit and thus it added more explanatory power to the achievement process of the Asians. The SOAG significantly predicted performance-approach, performance-avoidance and mastery-avoidance goals but had null relationship with mastery-approach goal. In the modified hierarchical, SOAG seemed to function as one of the forces motivating individuals to the individually oriented achievement goals. Data collected from a secondary school was used for culture related analysis. Age-wise, data collected from a primary school located in the same district was included and compared. It was found that test anxiety in primary school students was predicted only by SOAG but not by the other goals that are individually oriented. In the older age group, the SOAG’s effect on test anxiety was found to be mediated by the performance goal and master-avoidant goal endorsement. The nature of SOAG, as a predictor of individually oriented goals, and its effect on the three outcomes will be discussed in detail.